The Holistic Vision of Nursing in the Management of Friction Injuries Supported by the Nursing Interventions Classification - Elisiane De Oliveira Machado; Gabriel Heinzmann Diniz; Juciane Aparecida Furlan Inchauspe; Marla Andrieli Carvalho Barbosa (LPPM STIKes Muhammadiyah Ciamis, 2026)
The aging of the global population has led to an increasing incidence of skin tears (friction injuries) among hospitalized older adults, yet significant gaps in knowledge regarding prevention and holistic management of this condition persist among health professionals. This is a theoretical-reflective essay based on the academic and professional experiences of the authors, contextualized within the Brazilian nursing framework. No systematic inclusion/exclusion criteria were applied, and no delimited temporal scope was established, as the study draws upon theoretical foundations selected by the authors to address the topic comprehensively. The study identified three key risk factor domains for skin tears in older adults skin condition, mobility impairment, and general health status encompassing both intrinsic factors (age more than 60 years, polypharmacy, reduced skin turgor, impaired mobility) and extrinsic factors (inadequate bed linen, elevated headboard position, absence of a caregiver). A checklist tool was developed to enable systematic risk stratification (low, moderate, and high risk) and guide preventive nursing interventions aligned with the Nursing Interventions Classification (NIC) across four domains: basic physiological, complex physiological, behavioral, and safety. Holistic nursing care, grounded in structured assessment and evidence-based intervention, is essential to address skin tears in the elderly. The proposed checklist provides a simple, applicable tool to equip nurses, caregivers, and patients themselves for effective self-care and prevention of friction injuries in clinical and community settings.